Heat treatment to improve ductility of Ni-Cr-Co-Mo-Ti-Al alloys

A multi-step age-hardening heat treatment for HAYNES® 282® alloy enhances intermediate temperature ductility and confinement factors, addressing the limitations of conventional treatments and improving performance for gas turbine engine components.

JP7657886B2Active Publication Date: 2025-04-07HAYNES INTERNATIONAL
View PDF 18 Cites 0 Cited by

Patent Information

Application Number
JP2023187724
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2017-11-10
Filing Date
2023-11-01
Publication Date
2025-04-07
Estimated Expiration
2038-11-09

AI Technical Summary

Technical Problem

Conventional heat treatments for HAYNES® 282® alloy (UNS N07208) do not provide sufficient intermediate temperature ductility, which is critical for gas turbine engine components, especially in aircraft engines.

Method used

A new multi-step age-hardening heat treatment involving two primary steps: Step 1 at 843° C. (1550° F.) to 954° C. (1750° F.) and Step 2 at 704° C. (1300° F.) to 843° C. (1550° F.), with an optional Step 0 at 1010° C. (1850° F.) to 1066° C. (1950° F.), to enhance ductility and confinement factors at intermediate temperatures.

Benefits of technology

The new heat treatment significantly improves ductility and confinement factors at 760° C. (1400° F.), achieving higher values compared to conventional treatments without compromising strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007657886000010
    Figure 0007657886000010
  • Figure 0007657886000011
    Figure 0007657886000011
  • Figure 0007657886000012
    Figure 0007657886000012
Patent Text Reader

Abstract

To provide new age-hardening heat treatments for HAYNES(R)282(R)alloy (UNS N07208) which result in higher material ductilities and corresponding containment factors compared to those resulting from previously established heat treatments for the alloy.SOLUTION: In a method for heat treating alloy compositions within UNS N07028, the alloy composition is heated at a temperature between 843°C and 954°C for at least two hours, and then heated at a lower temperature between 704°C and 843°C for at least two hours. The alloy composition may be heated at a temperature between 1010°C and 1066°C for at least one hour before heating the alloy composition at a temperature between 843°C and 954°C.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to heat treatments applied to certain Ni-Cr-Co-Mo-Al-Ti alloy compositions of UNS N07208 that improve ductility compared to heat treatments for previously established alloys. In particular, these heat treatments improve ductility at intermediate temperatures, e.g., about 760° C. (1400° F.), which are important for the operation of gas turbine engine components requiring high ductility, particularly in aircraft engines. [Background technology]

[0002] HAYNES® 282® alloy is a commercial alloy of UNS N07208 used in many applications, particularly for components in both aircraft and industrial gas turbine engines. The alloy is nominally Ni-20Cr-10Co-8.5Mo-2.1Ti-1.5Al, but the composition range definition for this alloy is shown in Table 1. This alloy is notable for its unique combination of excellent creep strength, thermal stability, and fabricability. The excellent fabricability of HAYNES® 282® alloy includes excellent hot workability, cold workability, and weldability (both strain age cracking resistance and hot cracking resistance). [Table 1]

[0003] To achieve superior creep strength, 282® alloy is used in the age-hardened condition. The primary purpose of the age-hardening treatment is to precipitate / grow the gamma prime phase and increase the strength / hardness of the material (a process called age hardening). Typically, age hardening is performed on the alloy after it has been fully machined into a part and subjected to a post-machining "solution treatment". Solution treatment temperatures for 282® alloy are typically in the range of 1093°C-1149°C (2000-2100°F). The "standard age-hardening" treatment for 282® alloy is 1010°C (1850°F) for 2 hours + 788°C (1450°F) for 8 hours. This heat treatment is described in the introductory articles for 282® alloy (see, for example, Non-Patent Documents 1 and 2) as well as in the international specifications (called "precipitation heat treatment") (see Non-Patent Documents 3 and 4). The use of "single-step" age-hardening heat treatments has been explored for 282® alloy (see, e.g., "Alloy 282"). Typically, these single-step age-hardening treatments are performed at about 802°C (1475°F) for 4 to 8 hours. While both of the above thermal age-hardening heat treatments have received attention and are in service or in extensive test programs, it has been found that the intermediate temperature ductility resulting from either heat treatment may not be sufficient for all applications.

[0004] For certain components in gas turbine engines, and especially in aero engines, it is desirable to have as high intermediate temperature ductility as possible. These components, which may include certain cases and rings, need to have good containment properties in the event of engine failure. In addition to high strength, such containment properties depend heavily on the ductility of the alloy at the operating temperatures. Although the containment properties are best measured with costly special high strain rate tests, a reasonable measure of the containment properties is obtained by considering the ductility (elongation) values ​​obtained from standard tensile tests at the relevant temperatures. Yield strength (YS) and ultimate tensile strength (UTS) values ​​from tensile tests are also considered. The confinement factor, CF, can be calculated from the results of the tensile tests and is defined as CF=1 / 2*(YS+UTS)*(elongation). In applications where containment properties are required, a high value of CF is desired. When comparing CF values ​​for different material conditions, it is important to compare similar product shapes and sizes and use the same specimen geometry, since tensile properties can be highly dependent on the shape and size of the product, as well as the shape of the test specimen.

[0005] Given the fact that the underlying tensile properties are typically temperature dependent, the confinement factor is temperature dependent. For applications where confinement properties are important, the service temperature may fall in the "mid-range" between about 649°C (1200°F) and 816°C (1500°F). For this reason, a temperature of 760°C (1400°F) was selected for the present testing. Tensile properties and resulting CF values ​​at 760°C (1400°F) are shown in Table 2 for 282® alloy in both the "standard" and "single-step" age-hardened conditions. This table includes data only from 1.6 mm (0.063 in) thick plate (sheet). It can be seen that the "standard" age-hardened treatment (heat treatment code AHT1) results in a significantly higher CF than the single-step age-hardened condition (heat treatment code AHT0), i.e., 2751 vs. 1344. While both YS and UTS are slightly higher in the AHT1 condition, the biggest difference is the significant drop in ductility (elongation) in the AHT0 condition (26.0% vs. 12.9%). Although higher CF values ​​in the AHT1 condition are good, even higher CF values ​​are desirable in applications where containment properties are essential. The basis of this invention is the discovery of a new age-hardening heat treatment for 282® alloy that results in even greater ductility and corresponding CF values. [Table 2] [Prior art documents] [Patent documents]

[0006] [Patent Document 1] U.S. Pat. No. 8,066,938 [Non-patent literature]

[0007] [Non-Patent Document 1] LM Pike, “HAYNES 282 alloy - A New Wrought Superalloy Designed for Improved Creep Strength and Fabricability” ASME Turbo Expo 2006, paper no. GT2006-91204, ASME Publication, New York, NY, 2006. [Non-Patent Document 2] LM Pike, “Development of a Fabricable Gamma-Prime (γ') Strengthened Superalloy”, Superalloys 2008 - Proceedings of the 11th International Symposium on Superalloys, p 191-200, 2008 [Non-Patent Document 3] AMS Specification AMS5951 Rev. A, Nickel Alloys, Nickel Alloys, Corrosion and Heat Resistant, Sheet, Strip, and Plate, 57Ni-20Cr-10Co-8.5Mo-2.1Ti-1.5Al-0.005B, SAE International (2017) [Non-Patent Document 4] AMS Specification AMS5915, Nickel Alloys, Nickel Alloys, Corrosion and Heat Resistant, Bars and Forgings, 57Ni-20Cr-10Co-8.5Mo-2.1Ti-1.5Al-0.005B, SAE International (2014) [Non-Patent Document 5] SK Srivastava, JL Caron, and LM Pike. “Recent Developments in the Characteristics of Haynes 282 Alloy For Use in A-USC applications” Advances in Materials Technology for Fossil Power Plants: Proceedings from the Seventh International Conference, October 22-25, 2013 Waikoloa, Hawaii,USA, p. 120. ASM International, 2014 [Non-Patent Document 6] MG Fahrmann and LM Pike, “Experimental TTT Diagram of HAYNES 282 Alloy”, Proceedings of the 9th International Symposium on Superalloy 718 & Derivatives: Energy Aerospace and Industrial Applications, E. Ott et al. (Eds.), June 3-6, 2018, The Minerals, Metals, and Materials Society, 2018 Summary of the Invention [Problem to be solved by the invention]

[0008] It is a primary objective of the present invention to provide a new age-hardening heat treatment for HAYNES® 282® alloy (UNS N07208) that results in higher material ductility and corresponding Confinement Factor (CF) compared to those resulting from previously established heat treatments for the alloy. [Means for solving the problem]

[0009] The new heat treatment includes at least two steps. The first required step is a heat treatment within the temperature range of 843°C (1550°F) to 954°C (1750°F) (referred to herein as "Step 1"). The second required step is a heat treatment within the temperature range of 704°C (1300°F) to 843°C (1550°F) (referred to herein as "Step 2"). The minimum temperature within the range of Step 1 is the same as the maximum temperature within the range of Step 2 (843°C (1550°F)), but the temperatures of the two steps must be selected such that there is a temperature drop between the two steps. The duration of the two steps can vary depending on the size and shape of the product to be treated, but each step must be at least 2 hours. One example is 4 hours for the first step, followed by 8 hours for the second step. In addition to these two required steps, there is a step in the range of 1010°C (1850°F) to 1066°C (1950°F) (referred to herein as "Step 0") that may be optionally inserted before Step 1. The duration of this step may also vary, but may be, for example, about 1 to 2 hours. The above multi-step heat treatment has unexpectedly been found to provide 282® alloy with significantly improved ductility and corresponding confinement factors at the intermediate temperature of 760°C (1400°F) as compared to conventionally established heat treatments for the alloy. [Brief description of the drawings]

[0010] [Figure 1] 1 is a typical SEM image of the grain boundary layer (consisting of both M23C6 and gamma prime) formed when the alloy composition in UNS N07208 was heat treated according to this method. In this case, the heat treatment was AHT2. [Diagram 2] A typical SEM image of the grain boundary layers of discrete M23C6 carbides that result when the alloy composition in UNS N07208 is heat treated using the "standard" two-step age hardening heat treatment (AHT1). [Diagram 3]FIG. 1 is a typical SEM image of the grain boundary layer of continuous M23C6 carbides that occurs when the alloy composition in UNS N07208 is heat treated using a single-step age-hardening heat treatment (AHT0). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] A multi-step age hardening heat treatment is provided for alloy compositions within the UNS N07208 range that provides improved intermediate temperature ductility and corresponding confinement factors over previously established age hardening treatments for this alloy.

[0012] The multi-step heat treatment involves a step (Step 1) from 843°C (1550°F) to 954°C (1750°F) followed by a lower temperature step (Step 2) from 704°C (1300°F) to 843°C (1550°F). The duration of each step can vary, but an example is 4 hours for the first step and 8 hours for the second step. Optionally, a step can be inserted before Step 1. The temperature range for this step (Step 0) is 1010°C (1850°F) to 1066°C (1950°F). The duration of Step 0 can also vary, but an example is 2 hours. Table 3 shows the steps of the new heat treatment for 282® alloy. [Table 3]

[0013] A number of multi-step age hardening heat treatments were applied to specimens of 282® alloy. The specimens were prepared from 1.6 mm (0.063 inch) sheet that was mill annealed (solution treated) before being subjected to the various age hardening heat treatments. A list of the heat treatments that are part of this invention is shown in Table 4a along with a code to identify each treatment. Other heat treatments outside of this invention were also tested for comparison and are listed in Table 4b. [Table 4] [Table 5]

[0014] The heat treated samples were tensile tested at 760°C (1400°F) to determine their strength, ductility, and confinement factor at this critical temperature. The microstructures of selected samples were also examined using SEM (scanning electron microscope) to determine the effect of heat treatment on grain boundary precipitation within the alloy.

[0015] The tensile test results are shown in Table 5. The test results for AHT0 and AHT1 shown in Table 2 are reproduced here for comparison purposes. [Table 6]

[0016] The results show that all 17 heat treatments, AHT2-AHT5, AHT10, and AHT12-AHT23, have significantly increased ductility (elongation) values ​​compared to heat treatments AHT0 and AHT1. In fact, all of these 17 heat treatments resulted in tensile ductility values ​​greater than 30% (rounded to the nearest integer). In contrast, seven heat treatments, AHT0, AHT1, AHT6-AHT9, and AHT11, all resulted in tensile ductility values ​​less than 30%. Furthermore, when the 17 newly discovered heat treatments (AHT2-AHT5, AHT10, AHT12-AHT23) were subjected to the alloys, no significant change in strength was observed, only very slight changes in UTS (some slightly increased, others slightly decreased), and YS was in fact slightly increased in all 17 cases relative to AHT0 and AHT1. In contrast, both AHT6 and AHT7 resulted in a significant decrease in YS compared to the other heat treatments investigated. This is an unacceptable degradation of this important property, and therefore, neither AHT6 nor AHT7 are considered part of this invention. The combined effect of the significant increase in elongation, and the lack of any significant change in strength, was that the confinement factor (CF) was found to be significantly increased compared to AHT0 or AHT1 when subjected to any of the 17 heat treatments (AHT2-AHT5, AHT10, and AHT12-AHT23). This is a highly desirable result, and provides a distinct advantage to 282 alloy when used in applications requiring good confinement properties. Numerically, the CF values ​​of the 282 alloy sheet specimens resulting from the 17 heat treatments that are part of this invention were all found to be greater than 3275. In contrast, the CF values ​​resulting from the seven heat treatments that are not part of this invention were all less than 3275.

[0017] Of the 24 heat treatments considered in Table 5, 17 that are part of the present invention are AHT2-AHT5, AHT10, and AHT12-AHT23. As specified in Table 3, only these 17 heat treatments contain both step 1 and step 2, and only in those 17 heat treatments did the high ductility and CF values ​​that are the objective of the present invention be obtained.

[0018] To better understand the beneficial effects of the various steps in the heat treatment of the present invention, it is useful to consider the microstructures obtained by observing 282® alloy before and after heat treatment, first in the as-heat treated condition and then in the condition produced by conventional heat treatments (AHT0 and AHT1).

[0019] As Heat Treated: HAYNES® 282® alloy is normally sold in the as-heat treated (or mill annealed) condition. Typical heat treatment temperatures for 282® alloy range from 1093°C (2000°F) to 1149°C (2100°F). In this condition, negligible primary carbides / nitrides are present in the microstructure. There are essentially no secondary precipitations at the grain boundaries and within the grains. This has been explained in the published literature, including the technical article, “282® alloy: properties of alloy carbides and nitrides in the as-heat treated (or mill annealed) condition.”

[0020] AHT1: The microstructural characteristics resulting from the "standard" heat treatment (AHT1) are also described in this technical paper. The first step (1010 °C (1850 °F) / 2 hours) resulted in the formation of discrete M crystalline structures located at grain boundaries and grown in a "stonewall" configuration. 23 This resulted in the formation of C6 carbides. Note that 1010 °C (1850 °F) is well above the solvus temperature of gamma prime of 282 alloy at 982 °C (1827 °F). The second step of AHT1 (788 °C (1450 °F) / 8 hours) resulted in the formation of fine gamma prime phase uniformly distributed throughout the grains. The gamma prime was essentially spherical and approximately 20 nm in diameter. No significant accumulation or layers of gamma prime phase at the grain boundaries were observed. An SEM image of a typical 282 alloy grain boundary after AHT1 heat treatment is shown in Figure 2.

[0021] AHT0: The microstructural features resulting from the "single-step" heat treatment (AHT0) are described in the technical paper "AHT0" (Non-Patent Document 5). This treatment involves only one step (802°C (1475°F) / 8h). This step results in more continuous M at the grain boundaries compared to standard treatment.23 A C6 layer was formed. An SEM image of such a grain boundary is given in Figure 3. Also formed during this single-step heat treatment are spherical gamma primes with diameters of 38-71 nm, somewhat coarser than in the "standard" heat treatment. Also, no significant accumulation or layer of gamma prime phase is observed at the grain boundaries.

[0022] We now describe the microstructural features observed resulting from the heat treatment of the present invention, with each step considered separately.

[0023] Step 1 (843℃(1550°F)~954℃(1750°F)): This temperature range is well below the gamma prime solvus temperature of 982°C (1827°F) for 282® alloy and is therefore expected to form the gamma prime phase. Studies of material heat treated in the range 843°C (1550°F) to 954°C (1750°F) have shown that gamma prime does indeed form. Again, globular gamma prime precipitates are observed uniformly within the grains. However, in addition, discrete M 23 In addition to the C6 carbides, significant amounts of gamma prime phase are observed at the grain boundaries. These two phases together form a composite grain boundary layer. A typical SEM image of this grain boundary layer is shown in Figure 1. It is noted that such a layer was not found in either of the two previously established heat treatments for 282® alloy (AHT0 or AHT1). Although no specific mechanism is provided at this time, it is believed that the composite gamma prime+M phase formed during the heat treatment of the present invention. 23 The C6 grain boundary layers are believed to result in the improved intermediate temperature ductility and associated confinement factors which define the present invention. The presence of these grain boundary layers, and in particular their beneficial effect on the intermediate temperature ductility and confinement properties of 282® alloy, was unexpected and serves as the basis of the present invention.

[0024] Step 2 (704°C (1300°F) ~ 843°C (1550°F)): This temperature range is even lower than the solvus of gamma prime. Therefore, if step 2 is applied after step 1, the volume fraction of the gamma prime phase will continue to increase. This increase in gamma prime further strengthens the alloy and provides the high YS required for typical applications. Some additional M 23 Precipitation of C6 may also occur.

[0025] Step 0 (1010℃(1850°F)~1066℃(1950°F)): This step is considered an optional step in the heat treatment of the present invention and is applied before step 1. This step mirrors the first step of a "standard" heat treatment. Thus, the resulting microstructure is a discrete M 23 C6 stone wall structure. When steps 1 and 2 are applied, the microstructure also contains grain boundary gamma prime layers, as well as globular gamma prime present within the grains.

[0026] All of the heat treatments contemplated herein, including both Step 1 and Step 2 (as defined in Table 3), have been found to have the desired properties of improved intermediate temperature ductility and associated confinement factor, without any loss in strength. This is regardless of whether Step 0 is applied prior to Step 1. Such heat treatments include AHT2-AHT5, AHT10, and AHT12-AHT23. All of these are considered heat treatments of the present invention.

[0027] As mentioned above, the composite gamma prime + M at the grain boundary 23 The presence of the C6 layer is believed to be responsible for the improved intermediate temperature ductility and associated confinement factors in 282® alloy provided by the heat treatment of the present invention. Such a layer forms following application of the Step 1 configuration of the heat treatment. However, the present invention is not fully defined by the formation of the layer itself. For example, heat treated AHT6 contains composite gamma prime + M phases at the grain boundaries. 23AHT6 includes step 1, which provides the C6 layer. However, AHT6 does not include step 2. As a result, less strengthening gamma prime phase is formed and the YS is rather low. In fact, it is too low. Therefore, it is important to apply step 2 after step 1 to achieve the desired YS. Also, the ductility resulting from AHT6 is less than the desired 30%. The heat treatments of AHT9 and AHT11 are also single-step (only step 1). Like AHT6, neither AHT9 nor AHT11 have the desired 30% ductility. It seems that a single-step heat treatment does not provide the desired combination of acceptable YS and high ductility and CF values ​​in 282 alloy. It has been found that a heat treatment including at least two steps (defined as step 1 and step 2 in Table 3) is necessary to achieve such a combination of properties. Although the temperature ranges of step 1 and step 2 overlap at a temperature of 843° C. (1550° F.), the present invention does not encompass a heat treatment in which both step 1 and step 2 are at 843° C. (1550° F.) because the present invention requires a temperature reduction between the two steps. Such a heat treatment would be essentially the same as a single-step heat treatment such as AHT11, which would not meet the desired properties.

[0028] Compound Gamma Prime+M 23Another example where the mere presence of the C6 phase is not sufficient in itself is AHT7. This heat treatment includes a first step and a second step, but the first step is at a temperature that is too high (982°C (1800°F)) compared to the range of step 1 defined in Table 3 (maximum 954°C (1750°F)). However, the second step of AHT7 falls within step 2 defined in Table 3. However, although AHT7 is similar to the heat treatment of the present invention, the excessively high first step temperature results in a lower YS than the acceptable range. Without being bound to a particular mechanism, it is believed that this may be a result of the gamma prime formed at 982°C (1800°F) being too coarse, resulting in less effective strengthening. It is therefore important to keep step 1 below the upper limit specified in Table 3. In fact, the upper step 1 temperature is most preferably reduced to 927°C (1700°F) to further ensure that the gamma prime phase produced by the heat treatment is not too coarse.

[0029] Additional studies were conducted to better understand at what temperatures the gamma prime layer forms at the grain boundaries of 282® alloy. In this study, specimens of 282® alloy were heat treated for 10 hours at temperatures ranging from 649°C (1200°F) to 1093°C (2000°F). The specimens were examined by SEM to reveal the presence of gamma prime+M at the grain boundaries. 23 The C6 layer was searched for. The results are shown in Table 6. Gamma Prime + M 23The temperature range in which the C6 layer was found was 816 °C (1500 °F) to 982 °C (1800 °F). However, at 816 °C (1500 °F), the continuity of the gamma prime component of the layer appeared to be reduced. This fact, combined with the aforementioned AHT0 and AHT1 heat treatments, that no gamma prime was observed at the grain boundaries after exposure at 802 °C (1475 °F) and 788 °C (1450 °F), respectively, suggests that the lower boundary for the formation of a beneficial, almost continuous gamma prime layer is precisely at about 816 °C (1500 °F). It would therefore appear that to ensure a fully developed layer, the step 1 lower limit of 816 °C (1500 °F) should be comfortably above 843 °C (1550 °F). Since the upper limit for step 1 was found to be 954°C (1750°F) in the previous paragraph, the allowable temperature range for step 1 is 843°C (1550°F) to 954°C (1750°F). More preferably, to avoid excessive coarsening of the gamma prime phase, the allowable temperature range for step 1 may be further limited to 843°C (1550°F) to 927°C (1700°F). [Table 7]

[0030] In the previous two paragraphs, the acceptable temperature range for Step 1 was defined based on the microstructural discussion. The tensile data presented in Table 5 further supports the appropriateness of the Step 1 temperature range. For example, the upper limit of the range, 954°C (1750°F), is supported by the high ductility and CF values ​​obtained from AHT4 and AHT5. At the more favorable upper limit of 927°C (1700°F), the ductility and CF values ​​of the heat treated samples (AHT17 and AHT21) are also high. At the lower end of the Step 1 temperature range (843°C (1550°F)), it was found that heat treatments AHT10 and AHT18 resulted in higher ductility and CF values. Note that good tensile properties were found over the specified Step 1 temperature range, regardless of whether any Step 0 was performed prior to Step 1.

[0031] Step 1 temperatures outside the specified ranges may not result in the desired properties. For example, for AHT7, a step 1 temperature of 982°C (1800°F) is above the specified limits. In this case, not only were the ductility and CF values ​​too low (less than 30% and 3275, respectively), but the YS was also undesirably reduced compared to AHT1. Similarly, AHT8 is a heat treatment where the step 1 heat treatment of 816°C (1500°F) is below the specified limits. This heat treatment also results in ductility and CF values ​​that are too low.

[0032] As previously mentioned, the primary objective of step 2 is to complete the precipitation of gamma prime with the goal of increasing strength / hardness as much as possible. A published study, 2001, J. Appl. Phys. 1999, 141:1311-1350, 2001, investigated the effect of isothermal aging on the hardness of 282® alloy. Some additional testing was also performed by the authors. In summary, it was found that maximum hardness was achieved after aging in the range of about 732°C (1350°F) to about 816°C (1500°F). A similar isothermal hardening study was recently published, which is consistent with previous work (2001, J. Appl. Phys. 1999, 141:1311-1350, 2001). Hardness can be expected to roughly correlate with the YS of the alloy. Thus, based on the hardness data, the appropriate temperature range for step 2 of the heat treatment of the present invention is 732°C (1350°F) to 816°C (1500°F). However, it is clear from the tensile data in Table 5 that the step 2 range can be extended to include temperatures from 704°C (1300°F) to 843°C (1550°F). This is due to the fact that AHT12 and AHT19 (both of which have a step 2 temperature of 704°C (1300°F)) result in acceptable tensile properties, but the same is true for AHT16 and AHT20 (both of which include a step 2 temperature of 843°C (1550°F)).

[0033] The purpose of any step 0 is to form M at grain boundaries in a discrete stonewall-type configuration before forming gamma prime at the grain boundaries during step 1. 23The first step is to form C6. For this, the temperature needs to be comfortably above the gamma prime solvus of 982°C (1827°F). 1010°C (1850°F) has been consistently shown to be an acceptable temperature for producing such a structure, and therefore serves as the low temperature for Step 0. The upper limit for Step 0 needs to be somewhat lower than the heat treatment temperature, otherwise grain size will tend to coarsen during processing, which is undesirable for superior mechanical properties. Since heat treatment temperatures for 282® alloy are typically in the range of 1093°C (2000°F) to 1149°C (2100°F), the upper temperature limit needs to be kept at or below about 1066°C (1950°F). Thus, the Step 0 temperature range should be 1010°C (1850°F) to 1066°C (1950°F). The tensile data shown in Table 5 supports this range. For example, AHT2 is one of six different heat treatments tested where a lower Step 0 temperature limit of 1010°C (1850°F) resulted in good ductility and CF values. Similarly, AHT23 is an example where an upper Step 0 temperature limit of 1066°C (1950°F) resulted in good ductility and CF values. However, it should be noted that since very good containment properties were achieved with both the heat treatments with and without Step 0, this step is an optional and not required component of the heat treatment of the present invention.

[0034] As mentioned earlier in the text, when examining the effect of the new age hardening treatment, it is important to test material in the same product shape and size. The tensile tests reported in Table 5 were all performed on 1.6 mm (0.063 in) thick sheets. To more fully understand the effect of the new heat treatment, tests were also performed on both plate and ring material. First, the results of the 12.7 mm (0.5 in) plate heat treatment study are provided. In this study, 282 plate specimens (starting in the mill annealed condition) were subjected to the AHT1, AHT2, and AHT3 heat treatments. The results are given in Table 7. The two heat treatments of the present invention (AHT2 and AHT3) provided improved ductility and associated CF compared to AHT1, although not as dramatic as that seen in the sheet products. For example, AHT3 resulted in a 25% higher CF value than AHT1 (compared to a 63% increase for the sheet products). Nevertheless, the new heat treatments resulted in a significant difference. Furthermore, no significant loss of strength was observed. [Table 8]

[0035] The tensile properties of rolled rings (approximately 610 mm (24 in) diameter) subjected to solution treatment followed by different age hardening heat treatments were measured. The results are shown in Table 8. Again, the new heat treatments AHT2 and AHT3 significantly improved ductility and CF with little loss of strength. Compared to AHT1, the new AHT2 and AHT3 heat treatments improved CF over AHT1 by 14% and 26%, respectively, in the rolled ring samples. [Table 9]

[0036] Although the specimens tested were limited to forged sheet, plate, and ring, the new heat treatments can reasonably be expected to provide benefits for other product forms as well. These can include, but are not limited to, other wrought forms (bar, tubing, pipe, forgings, wire, etc.), and cast, spray formed, or powder metallurgical forms, i.e., powders, pressed powders, sintered powders, additively processed powders, etc. Thus, the present invention encompasses the heat treatments specified as applied to all product forms of 282® alloy (UNS N07208).

[0037] While all of the tests presented herein have been on HAYNES® 282® alloy (UNS N07208), it is believed that the beneficial results of the heat treatment of the present invention may be observed for alloys of similar composition, provided that the particular major phases precipitate at similar temperatures and in similar morphologies. An example would be the full range of compositions covered by U.S. Patent No. 5,399,633. However, it is not expected that such heat treatments would necessarily be effective for all alloys of the same general alloy classification as 282® alloy (which may be described as a weldable wrought nickel-based gamma prime former). This is because the different major phases (gamma prime, M 23 This is because the solvus temperatures of the phases (e.g., C6) vary significantly depending on the alloy, and the morphology of the phases formed can also be expected to vary widely depending on the alloy.

[0038] Although a specific preferred embodiment of the heat treatment has been disclosed, it should be clearly understood that the invention is not limited thereto and that various embodiments may be made within the scope of the following claims.

Claims

1. A method for heat treating an alloy, comprising the steps of: 18.5 to 20.5% chromium, 9.0 to 11.0% Cobalt, 8.0 to 9.0% molybdenum, 1.38 to 1.65% Aluminum, Maximum 1.5% iron, 1.90-2.30% titanium, 0.04 to 0.08% carbon, Maximum 0.15% silicon, Phosphorus up to 0.015% Maximum 0.015% sulfur, 0.003 to 0.010% boron, 0.2% max Niobium, Maximum 0.5% tungsten, Maximum 0.1% Tantalum, Maximum 0.1% copper, Maximum 0.3% Manganese, Maximum 0.1% Zirconium, and the balance being nickel, said heat treatment method comprising: heating the alloy at a temperature of 843°C to 954°C (1550°F to 1750°F) for at least 2 hours; Next, heating the alloy at a low temperature between 704°C and 843°C (1300°F and 1550°F) for at least 2 hours. and The heat treatment method thereby forms an alloy having a complex grain boundary layer containing gamma prime and M 23 C 6 carbides.

2. The heat treatment method of claim 1, further comprising the step of heating the alloy at a temperature of 1010°C to 1066°C (1850°F to 1950°F) for at least 1 hour before heating the alloy at a temperature of 843°C to 954°C (1550°F to 1750°F).

3. The heat treatment method of claim 1, wherein the step of heating the alloy at a temperature of 843°C to 954°C (1550°F to 1750°F) includes the step of heating the alloy to a temperature of 899°C (1650°F) and holding at that temperature for four hours.

4. The heat treatment method of claim 1, wherein the step of heating the alloy at a temperature of 704°C to 843°C (1300°F to 1550°F) includes the step of heating the alloy at a temperature of 788°C (1450°F) for 8 hours.

5. The heat treatment method of claim 1, further comprising the step of heating the alloy at a temperature of 1010°C (1850°F) for two hours prior to the step of heating the alloy at a temperature of 843°C to 954°C (1550°F to 1750°F).

6. The heat treatment method of claim 1, wherein the alloy in the form of a thin plate 1.6 mm (0.063 inch) thick has an elongation of 30% or more at 760°C.

7. The method of claim 1, further comprising the steps of: heating the alloy at a temperature of 843°C to 927°C (1550°F to 1700°F) for at least 4 hours; 7. The heat treating method of claim 6, further comprising the step of heating the alloy at a temperature of 1010°C to 1066°C (1850°F to 1950°F) for at least one hour prior to heating the alloy at a temperature of 843°C to 927°C (1550°F to 1700°F).

8. The heat treatment method of claim 7, wherein the step of heating the alloy at a temperature of 843°C to 927°C (1550°F to 1700°F) includes the step of heating the alloy to a temperature of 899°C (1650°F) and holding at that temperature for four hours.

9. The heat treatment method of claim 7, wherein the step of heating the alloy at a temperature of 704°C to 843°C (1300°F to 1550°F) includes the step of heating the alloy at a temperature of 788°C (1450°F) for 8 hours.

10. The heat treatment method of claim 7, further comprising the step of heating the alloy at a temperature of 1010°C (1850°F) for two hours prior to the step of heating the alloy at a temperature of 843°C to 927°C (1550°F to 1700°F). Heating the alloy at a temperature of 843°C to 954°C (1550°F to 1750°F) for at least 6 hours. The heat treatment method of claim 1 , comprising:

12. The heat treatment method of claim 11, further comprising the step of heating the alloy at a temperature of 1010°C to 1066°C (1850°F to 1950°F) for at least one hour prior to heating the alloy at a temperature of 843°C to 954°C (1550°F to 1750°F).

13. The heat treatment method of claim 11, wherein the step of heating the alloy at a temperature of 843°C to 954°C (1550°F to 1750°F) includes the step of heating the alloy at a temperature of 899°C (1650°F).

14. The heat treatment method of claim 11, wherein the step of heating the alloy at a temperature of 704°C to 843°C (1300°F to 1550°F) includes the step of heating the alloy at a temperature of 788°C (1450°F) for 8 hours.

15. The heat treatment method of claim 11, further comprising the step of heating the alloy at a temperature of 1010°C (1850°F) for two hours prior to the step of heating the alloy at a temperature of 843°C to 954°C (1550°F to 1750°F).

16. The heat treatment method of claim 1, wherein the alloy in the form of a 1.6 mm (0.063 inch) thick sheet has a confinement factor of 3275 or greater at 760°C.

Citation Information

Patent Citations

  • AMS5915

  • AMS5951

  • High-strength and high-toughness heat-resistant alloy for ultra-supercritical steam turbine rotor, and preparation method thereof

    CN106929710A

  • Ni-Cr-Co ALLOY FOR ADVANCED GAS TURBINE ENGINE

    JP2006070360A

  • HIGH-STRENGTH Ni-BASED FORGED SUPERALLOY, AND METHOD FOR PRODUCING THE SAME

    JP2011084812A